SKELETAL MUSCLE FATIGABILITY PREDICTS PHYSICAL FUNCTION IN MOBILITY-LIMITED OLDER ADULTS. (11th November 2018) - Grosicki, G; Englund, D; Price, L; Iwai, M; Kashiwa, M; Liu, C; Reid, K; Fielding, R
Abstract: We previously demonstrated that progressive resistance training (PRT) improves lower-extremity skeletal muscle fatigability in mobility-limited older adults. The objective of this study was to examine the relationship between lower-extremity fatigability and physical function, and assess the downstream functional implications of PRT-mediated fatigability improvements in mobility-limited older individuals. Seventy mobility-limited (Short Physical Performance Battery (SPPB) ≤9) older adults (78.9 ± 5.4 yrs) were randomized to PRT or home-based flexibility 3 days/week for 12 weeks. Lower-extremity muscle fatigue was defined as the sum of peak torques from an isokinetic knee extension fatigue test. Relationships between muscle fatigue and both performance-based and patient-reported physical function were examined using partial correlations adjusted for age, sex, and body mass index. Skeletal muscle fatigability was a significant predictor of six-minute walk distance and stair climb time (P<0.05), explaining 10 and 30% of the variance, respectively. PRT-mediated improvements in skeletal muscle fatigability were paralleled by increases (P<0.05) in self-reported activity participation (+20%) and lower extremity function (+7%), and associated with (P<0.05) improvements in SPPB score (r=0.32) and perceived fatigue tolerance (r=0.38). We establish skeletal muscle fatigability as a proximal determinant of physical function in mobility-limited older individuals. Given this finding, large-scale clinical trials utilizing therapeutic interventions to improve skeletal muscle fatigability as a strategy to improve functional capacity in older adults are of interest.